(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2006)
Carboxymethylcellulose (CMC)/chitosan microparticles containing vitamin E were prepared by a complex coacervation method and their potential use as a topical delivery system was evaluated. Morphology, particle size distribution, encapsulation yield, physical and chemical stability, in vitro release and permeation through skin were studied. The microparticles appeared to be spherical, with a homogeneous surface and were not aggregated. Mean diameters ranged from 2.7 to 7.6 µm and the encapsulation yield was 81%. Chemical stability studies indicated a protection of encapsulated vitamin E, of 8.1% for O/W and of 10.83% for W/O emulsions, following storage at 45 °C for 60 days. Forty-eight% of vitamin E, determined by HPLC, were released within 24 hours. In vitro permeation and retention studies showed a higher penetration rate of vitamin E in the free and encapsulated forms, from the W/O emulsion. The carriers studied seem to be promising systems for topical administration.